Study of Temperature and Concentration Dependence of Refractive Index of Liquids Using a Novel Technique - Subedi, D.P.; Adhikari, D.R.; Joshi, U.M.; Poudel, H.N.; Niraula, B. (Kathmandu University Journal of Science, Engineering and Technology, 2006)
A simple and reliable method of measuring the refractive index of liquids is reported in the present paper. The technique was employed to study the temperature dependence of refractive index of water (at sodium D-line 589nm). By measuring the refractive index of water at different temperatures, the temperature coefficient of refractive index (dn/dT) was determined. In addition to this, refractive index of different solutions as a function of the concentration was studied. The results were compared with the results obtained from commercial refractometers and it was found that this technique is quite reliable and can be safely used in the study of the optical properties of any transparent liquids.